Pathological In Vivo Analysis of Helicobacter DNA Infection in Stomach Cells Using Carbon Nanotube Microsensor - Kyung Lee; Sihyun Jun; Yeseul Oh; Seojun Lee; Ye Jun Oh; Keum Sook Kim; Suw Young Ly (Microorganisms)
The WHO has classified Helicobacter pylori as a group 1 carcinogen for stomach cancer since early 1994. However, despite the high prevalence of Helicobacter pylori infection, only about 3% of infected people eventually develop gastric cancer.Biomolecular detections of Helicobacter pylori(HP) were compared using specially modified sensors and fluorine immobilized on a carbon nanotube (HFCNT) electrode, which yielded sensitive results. Handheld voltammetric circuits were used for optimization. An anodic voltammogram of HP molecular oxidation was obtained at 0.0 V ± 0.1 (versus the Ag/AgCl/KCl) in a 0.1 ± 0.2 M NH4H2PO4 electrolyte solution. Under optimized conditions, the analytical working range was 2.98 × 103–22.127 × 10−3 CFU/mL HP using square wave (SW) stripping voltammetry, precision of R2 = 0.9857 ± 0.0005 (SWSV), the detection limit approached to 2.5 × 102 CFU/mL HP (S/N = 3).The developed techniques have been applied to diagnosis of early-stage HP infections using stomach tissue from healthy humans and gastric patients.